Prognostic Factor Of Local Recurrence, Metastasis, And Survival Rate In Squamous Cell Carcinoma Of The Lip, Ear, Skin And Comparison Of Retreatment Rotary Files And Ultrasonics For Removing Gutta Percha - Sahoo, Alkananda; Khan, Sabahat Hafiz; Nasti, Shahzaib; Mohkar, Sagar Haridas; Dhawan, Rajan; Panigrahi, Antarmayee (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess the prognostic factors of local recurrence, metastasis, and survival rate in squamous cell carcinoma of the lip, ear, skin and comparison of retreatment rotary files and ultrasonics for removing gutta percha. Material and methods: In this study, there were 50 cases of squamous cell carcinoma and 50 mandibular premolars with single canal for removing gutta percha had been gathered. The purpose of this study was to assess the prognostic factors for recurrence, metastasis and survival rate of squamous cell carcinoma of ear, skin and lips. The other goal of this study was to assess the comparison of retreatment rotary files and ultrasonics for removing gutta percha. The findings of the carcinoma cases had been studied and tabulated. For retreatment, two groups were made based on the technique of removing gutta percha. The first group comprised of 25 teeth in which ultrasonics were used and the 2nd group comprised of 25 cases in which Neo Endo retreatment rotary files were used. After cleaning all the teeth with 5.25% NaOCl and 17% EDTA, the canals were dried and obturation was done using AH Plus sealer. Neo endo retreatment files and ultrasonics were used to remove the gutta percha. To assess the remaining restoration material in the canals, stereomicroscopic evaluation was done under 100x magnification. The findings had been tabulated. Statistical analysis was conducted using SPSS software. Results: Tumor size of over 2 cm was seen in 21 cases. This was the most common prognostic factor for recurrence of squamous cell carcinoma. Depth of invasion of over 14 mm was seen in 14 cases. Undifferentiated tumors were also one of the reasons in 11 cases. Perineural invasion and lymphovascular invasion were seen in 5 and 1 case, respectively. It was observed that no modality removed the entire gutta percha from the canal. However, ultrasonics removed more amount of material form the canal in comparison to Neo Endo retreatment rotary files. Conclusion: The chief prognostic factor for recurrence of squamous cell carcinoma of, ear and akin was found to be the larger tumor size. Other factors were perineural invasion, lymphovascular invasion, depth of invasion and undifferentiated tumor. For removing the gutta percha, ultrasonics proved to be better than retreatment rotary files as the remaining amount of material was more when it was removed using retreatment rotary files.